Disposition of Cefquinome in Turkeys (Meleagris gallopavo) Following Intravenous and Intramuscular Administration - Mohamed Elbadawy; Ahmed Soliman; Amira Abugomaa; Adel Alkhedaide; Mohamed Mohamed Soliman; Mohamed Aboubakr (MDPI AG, 2021)
The bioavailability and pharmacokinetics in turkeys of cefquinome (CFQ), a broad-spectrum 4th-generation cephalosporin antibiotic, were explored after a single injection of 2 mg/kg body weight by intravenous (IV) and intramuscular (IM) routes. In a crossover design and 3-weeks washout interval, seven turkeys were assigned for this objective. Blood samples were collected prior to and at various time intervals following each administration. The concentration of CFQ in plasma was measured using HPLC with a UV detector set at 266 nm. For pharmacokinetic analysis, non-compartmental methods have been applied. Following IV administration, the elimination half-life (t1/2ʎz), distribution volume at steady state (Vdss), and total body clearance (Cltot) of CFQ were 1.55 h, 0.54 L/kg, and 0.32 L/h/kg, respectively. Following the IM administration, CFQ was speedily absorbed with an absorption half-life (t1/2ab) of 0.25 h, a maximum plasma concentration (Cmax) of 2.71 μg/mL, attained (Tmax) at 0.56 h. The bioavailability (F) and in vitro plasma protein binding of CFQ were 95.56% and 11.5%, respectively. Results indicated that CFQ was speedily absorbed with a considerable bioavailability after IM administration. In conclusion, CFQ has a favorable disposition in turkeys that can guide to estimate optimum dosage regimes and eventually lead to its usage to eradicate turkey's susceptible bacterial infections.